2009
DOI: 10.1068/a40266
|View full text |Cite
|
Sign up to set email alerts
|

Rationalising the Policy Mess? Ex Ante Policy Assessment and the Utilisation of Knowledge in the Policy Process

Abstract: Procedures for the ex ante assessment of public policies are currently in vogue across the OECD. Their design is typically informed by a rational-instrumental model of problem solving, which assumes that knowledge is collected, evaluated, and then translated straightforwardly into ‘better policies’. But this model has been little affected by more than three decades of academic research which has demonstrated that the reality of everyday policy making is far messier. In this paper we analyse whether the uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 17 publications
4
93
0
10
Order By: Relevance
“…Whereas the ecosystem goods and services concept aims for a better consideration of ecological and social complexities in environmental management (among others, see Fischer et al 2007), the majority of ex-ante assessment tools actually used in policy processes are of a rather simple and modest type (Nilsson et al 2008, Hertin et al 2009). More complex tools, on the other hand, have often remained black boxes to policy makers rather than transparent analytical tools that could effectively inform policy decisions (De Smedt 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the ecosystem goods and services concept aims for a better consideration of ecological and social complexities in environmental management (among others, see Fischer et al 2007), the majority of ex-ante assessment tools actually used in policy processes are of a rather simple and modest type (Nilsson et al 2008, Hertin et al 2009). More complex tools, on the other hand, have often remained black boxes to policy makers rather than transparent analytical tools that could effectively inform policy decisions (De Smedt 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rationality requires consistent behaviour in accordance with an individual's cognitive construct. A recent study looks at Impact Assessments as typically informed by an instrumentally rational model of problem solving, which assumes that knowledge is collected, evaluated and then translated straightforwardly into 'better policies' (Hertin et al 2009). This model has, according to the authors, been little affected by more than three decades of academic research, which has demonstrated that the reality of every-day policy-making is far messier.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical studies explored the reliance of Impact Assessments on the knowledge and expertise of those individuals responsible for carrying them out. For instance, it has been demonstrated that the educational background of officials can determine the Impact Assessment output (Hertin et al 2009). Those European Commission officials with an educational background in disciplines characterised by qualitative methods may encounter more difficulty in dealing with quantitative assessment techniques than those whose educational background embraces quantitative methods, e.g.…”
Section: Setting Objectivesmentioning
confidence: 99%
“…Among these, Sustainability Impact Assessments (SIA) is a major approach fostered by the European Union for assessing economic, social and environmental impacts of policy or rules-measures changes, as well as to assist decision-makers in sustainability contexts (Kirkpatrick and Lee 2002;George and Kirkpatrick 2003;Ness et al 2007). SIA experience has been gained in the past decade (Pope et al 2004;Nilsson et al 2008;Weaver and Jordan 2008;Hertin et al 2009) particularly as regards the use of indicators in SIA (Dilly and Hüttl 2009;Paracchini et al 2011).…”
Section: Introduction: Role Of Indicators In Sustainability Impact Asmentioning
confidence: 98%